Windows into Work from Home in Higher Education Institutions: Challenges of New Normal Culture in Management - Asif, Mahbub Karim; Hock, Oo Yu; Joseph, Adaikalam (2021)
The least one would expect of an academic institution of higher learning, as a provider of knowledge delivery and practice – depending on the nature, curricula, programs and standard operating procedure (SOP) governance and compliance, is to become increasingly immersed in the advocacy-practice of new normal culture ensuing the COVID-19 pandemic lockdowns, prohibitive policy requirements, emaciated businesses and atrophied consumerism, and restrictive mobility in public places and premises of business complexes including the so-called ‘corridors of knowledge’ or the old ‘ivory tower’ of yesteryears. ‘Work from Home’ (WFH) has never been the same again since the concept, years ago in good economic times and experimental employer-employee models of working-managing choices, started as an option of the corporate world to allow its employees to improve productivity with the liberty of WFH environment. Today, under the hovering cloud of death-threatening COVID epidemic and the virusvaccination against its host of mutations, WFH is reshaped by a culture of new norms touted as ‘new normal’. The prevailing normative culture and conventional SOPs of higher institutions of learning are, and its delivery of crisis management results must now become, a phenomenological expression of the new reality to operate education more effective and efficiently. It is no longer an issue of retaining competitiveness or to claim the trophy of competitive advantage. It is more than an issue of survival but essentially a solution-driven commitment to grow a new direction for education delivery of content, methods and other paraphernalia of teaching-learning tools for beneficiaries, communities, societies and country to generate new values and winning strategies in the public interest. In this paper, ‘iSOS’ (institutional Survival on Sustenance) and ‘iSOWS’ (institution Solutions of Winning Strategies) are tendered as value-conserving and value-creating complementary platforms, without compromising the fundamental philosophical foundation of education per se, to turnaround the inertia of COVID-19 inhibitive disruptions in the management and delivery of the higher education chain of business continuity.